Prenatal Prognostication of Congenital Diaphragmatic Hernia: What are we Looking at? - M Koehler Shannon; Amin Ruchi; R Gross Erica; Peterson Erika; Boyd Kevin; J Wagner Amy (Journal of Fetal Surgery, 2017)
Introduction: Data support the use of both ultrasound (US) and magnetic resonance imaging (MRI) in the prenatal prognostication of congenital diaphragmatic hernia (CDH). The aim of this study was to examine our experience and learning curve with both of these diagnostic tools in the setting of a new fetal program. Materials and Methods: This is a case series performed as a quality improvement measure. Fetuses were identified at a single tertiary institution with both ultrasound lung-to-head ratio (LHR) and MRI fetal lung volume from December 2012 until July 2016. Prenatal and postnatal data were collected. Statistical analysis was performed and a p-value of <0.05 was considered significant. Results: Twenty-one patients met inclusion criteria. Inaccurate LHRs were found in 26.9% (7/26) of patients, with the lack of a four-chamber heart view as the most common inaccuracy (5/26, 19.2%). Patients with only some or no stomach in the thoracic cavity on fetal MRI had 100% survival to discharge. Discussion: Accurate prenatal prognostication of CDH is challenging. We identified a pitfall in attaining LHR that can be easily identified, and that may influence the accuracy of the measurement. Furthermore, stomach position on MRI is a relatively newly described quick, easy, and reproducible metric for predicting prognosis.
Keywords: Congenital diaphragmatic hernia